2014
DOI: 10.1183/20734735.007813
|View full text |Cite
|
Sign up to set email alerts
|

How to: Bronchial thermoplasty in asthma

Abstract: • Bronchial thermoplasty, which involves the delivery of radio frequency energy to the airways, is a nonpharmacological intervention developed for the treatment of patients with moderate-to-severe asthma that is poorly controlled despite maximal therapy• Randomised controlled clinical trials of bronchial thermoplasty in patients with moderate and severe asthma have shown modest improvements in asthma quality of life and clinically worthwhile reductions in severe exacerbations and emergency department visits• T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…After 1 year of follow-up, a significant improvement in the Asthma Quality of Life Questionnaire score and a reduction in the rate of hospitalisations for asthma were observed in the thermoplasty group compared with the placebo group. In this trial, as in other, smaller studies, no improvement in lung function was observed [100]. In these studies, all the patients had a baseline FEV1 greater than or equal to 60% of the predicted value.…”
Section: Thermoplastysupporting
confidence: 57%
See 1 more Smart Citation
“…After 1 year of follow-up, a significant improvement in the Asthma Quality of Life Questionnaire score and a reduction in the rate of hospitalisations for asthma were observed in the thermoplasty group compared with the placebo group. In this trial, as in other, smaller studies, no improvement in lung function was observed [100]. In these studies, all the patients had a baseline FEV1 greater than or equal to 60% of the predicted value.…”
Section: Thermoplastysupporting
confidence: 57%
“…Three divided sessions are required to treat all the bronchi >3 mm in diameter, avoiding the middle lobe. The mechanism of action has been partially elucidated in animal and human studies, with demonstration of a reduction in airway smooth muscle mass [100,101].…”
Section: Thermoplastymentioning
confidence: 99%
“…Details are described elsewhere [Bicknell et al 2014]. There are currently no data on factors that predict a good response to BT.…”
Section: Discussionmentioning
confidence: 99%
“…The model examines a single human lung for reasons of computational complexity, choosing the left lung to avoid complicating effects of the untreated right middle lobe (3). In this study, we compare our patient specific methods (further described below) to current clinical practice (CCP) treatment across three full bronchial thermoplasty sessions.…”
Section: Methodsmentioning
confidence: 99%
“…However, BT is not successful in all patients. Current clinical practice involves the treatment of a standard set of airways at specific anatomic locations applied across three separate bronchoscopy procedures at one month intervals (3). This approach is essentially performed "blind" in that the choice of which airways to treat is not driven by structural or functional data to detect optimal treatment sites.…”
Section: Introductionmentioning
confidence: 99%